Mothers Beliefs and Dengue Haemorrhagic Fever (DHF) Preventive Behavior in Jagakarsa District - Sri Gusni Febriasari; Dianti Endang Kusumawardhani (Inquiry: Jurnal Ilmiah Psikologi, 2019)
Dengue Hemorrhagic Fever (DHF) is a public health problem in the world. Dengue control and prevention highly depend on vector control, Aedes Aegypti since no vaccine has been found for prevention. Effective, sustained community participation for dengue prevention remains a challenge in Jagakarsa District. This study explored perceptions of DHF preventive behavior as well as preventive behaviors among mothers in Jagakarsa District. The finding may be used to develop messages for improving DHF preventive behavior. This study uses descriptive study design by collecting data qualitatively through semi-structured interviews using the basic theory of the Health Belief Model (HBM). This research was conducted in September-October 2018. The finding of the study is the percieve of barriers that were greater than the perceive of benefits among mothers in Jagakarsa Subdistrict making mothers have a likelihood not to perform DHF preventive behavior such as don’t clean water container regularly and hanging used clothes outised cupboard.  The conclusion of this study is intervention needed in giving messages by considering perceive of benefits and barriers as well as giving messages via mobile phone channels (WhatsApp applications) that can improve DHF preventive behavior.